WEB GIS: The Promotion Model of Ngerangan Tourist Village in Klaten Regency through The Sustainable Rural Tourism Context During The Covid-19 Pandemic - Novia Sari Ristianti; Nurhadi Bashit; Desyta Ulfiana; Kurniawan Teguh Martono (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
The application of large-scale social restrictions (LSSR) during the Covid 19 pandemic in Indonesia significantly impacted the tourism sector. A Sustainable Rural Tourism model is expected to develop tourist village development during the Covid 19 pandemic through the WEB GIS (Website Geographical Information Systems) approach. It creates smart tourism through tourist information systems integrated with tourist websites. Ngerangan Tourist Village in Klaten Regency is a village where most of the population's economy is dependent on MSME (Micro, Small, and Medium enterprises) and farming activities. The research aims to formulate a tourism promotion model in Ngerangan tourism village through WEB GIS. The method used is quantitative. First, identifying the data needs such as spatial data (tourist attractions, tourist safety routes types, and infrastructure for implementing health protocols) and non-spatial data (information on MSME and virtual tours). Second, designing the tourism promotion system through WEB GIS and third, testing to see the output of the WEB GIS produced. The research output is  Web GIS using story maps application contains two spatial information about the Ngerangan tourist village. First, spatial information about tourist attractions includes locations, photos, and descriptions of tourist attractions. Second, spatial information regarding health protocols facilities during the Covid-19 pandemic includes locations, photos, and descriptions of health protocol facilities